Peran Media Sosial dalam Penyebaran Nilai-Nilai Islam di Era Globalisasi - Syifa Kholish Fadhilah; Rachela Qesya Maftuhah; Azkia Kailani Khairunnisa; Farid Multahadi (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
The religion of Islam, revealed to the Prophet Muhammad, continues to evolve over time, with Indonesia being a Muslim-majority country with a population of approximately 229.62 million people (87.2% of the total population). With the world's Muslim population projected to reach 2.2 billion by 2030, Indonesia accounts for around 13.1% of the global Muslim population. This study aims to examine the role of social media as a means of da'wah, the challenges faced, and solutions to overcome these challenges. Through a survey involving 76 respondents, it was found that the utilization of social media for Islamic da'wah content is still relatively low; the majority of respondents only occasionally search for and rarely share da'wah content. Challenges in da'wah in the era of globalization include laziness to access content, diverse preferences for preachers and methods, and the existence of invalid content. The findings suggest the need for more effective strategies to increase public interest and participation in da'wah through social media